Differences in joint power distribution in high and low lactate threshold cyclists - Leary, Brian K.; Burton, Heath M.; Vardarli, Emre; Wolfe, Anthony S.; Crawford, Charles K.; Akins, John D.; Coyle, Edward F. (European journal of applied physiology, 2021)
Purpose The biomechanical differences between cyclists with a high compared with a low blood lactate threshold (HLT; 80% V O 2max vs LLT, 70% V O 2max ) have yet to be completely described. We hypothesize that HLT cyclists reduce the stress placed on the knee extensor muscles by increasing the relative contribution from the hip joint during high-intensity cycling. Method Sixteen well-trained endurance athletes, with equally high V O 2max while cycling and running completed submaximal tests during incremental exercise to identify lactate threshold ( LT V O 2 ) while running and cycling. Subjects were separated into two groups based on % V O 2max at LT during cycling (high; HLT: 80.2 ± 2.1% V O 2max ; n = 8) and (LLT: 70.3 ± 2.9% V O 2max ; n = 8; p < 0.01). Absolute and relative joint specific powers were calculated from kinematic and pedal forces using inverse dynamics while cycling at intensities ranging from 60–90% V O 2max for between group comparisons. Result There was no difference between HLT and LLT in LT V O 2 ( p > 0.05) while running. While cycling in LLT, knee joint absolute power increased with work rate ( p < 0.05); however, in HLT no changes in knee joint absolute power occurred with increased work rate ( p > 0.05). The HLT generated significantly greater relative hip power compared with the LLT group at 90% V O 2max ( p < 0.05). Conclusion These data suggest that HLT cyclists exhibit a greater relative hip contribution to power output during cycling at 90% V O 2max . These observations support the theory that lactate production during cycling can be reduced by spreading the work rate between various muscle groups.